Impacto de los recursos de multimedia en la enseñanza de los estudios sociales, en los estudiantes del décimo año de educación básica del colegio nacional técnico industrial Dr Demetrio Aguilera Malta del cantón Santa Rosa en el año lectivo 2012-2013 - Moncada Peña, Rosa Nancy (2013)
Today we noticed how different areas of social axis have evolved and transforming governed by different aspects such as technological progress and development, the latter being one of the most influential in all areas of human action, including the field of education phenomena. The eminently suitable for the process of teaching and learning, which seeks to positively transform the educational process, through these new resources, technological incursion would be achieved, the teacher addresses in creative and attractive teaching and the student captures an easier and meaningful for the production of new knowledge form.